2018
DOI: 10.1177/1535370218784539
|View full text |Cite
|
Sign up to set email alerts
|

Shock waves increase pulmonary vascular leakage, inflammation, oxidative stress, and apoptosis in a mouse model

Abstract: Severe lung damage is a major cause of death in blast victims, but the mechanisms of pulmonary blast injury are not well understood. Therefore, it is important to study the injury mechanism of pulmonary blast injury. A model of lung injury induced by blast exposure was established by using a simulation blast device. The effectiveness and reproducibility of the device were investigated. Eighty mice were randomly divided into eight groups: control group and 3 h, 6 h, 12 h, 24 h, 48 h, 7 days and 14 days post bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…The results of the present study demonstrated that blast exposure not only caused signi cant hemorrhage, edema, and in ammatory cell in ltration, but also greatly increased the expression of TNFα, IL-1β and TGFβ1, and reduced the expression of IL-10 in the lungs. It has been reported that blast exposure led to an early in ammatory response, accompanied by signi cant oxidative stress and apoptosis in lung tissue cells [28]. A similar study also found that blast exposure signi cantly increased the expression of systemic pro-in ammatory and anti-in ammatory cytokines, and signi cantly caused pulmonary edema, in ammation, endothelial damage, and bleeding.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The results of the present study demonstrated that blast exposure not only caused signi cant hemorrhage, edema, and in ammatory cell in ltration, but also greatly increased the expression of TNFα, IL-1β and TGFβ1, and reduced the expression of IL-10 in the lungs. It has been reported that blast exposure led to an early in ammatory response, accompanied by signi cant oxidative stress and apoptosis in lung tissue cells [28]. A similar study also found that blast exposure signi cantly increased the expression of systemic pro-in ammatory and anti-in ammatory cytokines, and signi cantly caused pulmonary edema, in ammation, endothelial damage, and bleeding.…”
Section: Discussionmentioning
confidence: 54%
“…Our previous studies found that blast injury caused a signi cant increased expression of interleukin-1 (IL-1β), IL-6 and tumor necrosis factor (TNF-α), a signi cant decreased expression of IL-10, an increase in Evans blue leakage, and an signi cant increase in in ammatory cell in ltration [14][15][16]. In addition, we have previously reported that blast exposure-induced in ammation in the lungs occurred within the rst 12-48 h and peaked at approximately 24 h [17]. Jason Smith et al [18] reported similar results that in ammation affected the lungs, which developed from 24 h to 48 h and peaked at about 48 h. However, current treatment plan for patients with lung blast injury mainly focuses on supportive care, intensive therapy and mechanical ventilation, and there is no speci c alternative therapy.…”
mentioning
confidence: 99%
“…It suggested that cantharidin may inhibit PP2A activation by increasing SOD level. 2) In the general state, the tissue would increase the SOD and GSH level to protect cells from ROS damage in a short time, but ultimately reduced SOD and GSH level because of the continued consumption [ 29 , 30 ]. Considered that we took blood in an early time, it is possible.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β, IL-6, and TNF-α are pro-inflammatory cytokines, while IL-10 is an anti-inflammatory cytokine. Tong et al [ 93 ] found that the mRNA and protein expression of IL-1 β, IL-6, and TNF-α increased, while the mRNA and protein expression of IL-10 decreased after PBLI, indicating the occurrence of inflammation. IL-1β, IL-6, IL-10, and TNF-α are extensively used as biomarkers to assess the degree of inflammatory response and are indicators of whether the treatment method has anti-inflammatory effects.…”
Section: Damps and Their Signaling Pathways Related To Pblimentioning
confidence: 99%